Retinoic acid-metabolizing enzyme cytochrome P450 26A1 promotes skin carcinogenesis induced by 7,12-dimethylbenz[a]anthracene - Osanai, Makoto (Oncol Lett, 2018)
Elevated expression of the retinoic acid-metabolizing enzyme cytochrome P450 26A1 (CYP26A1) has been demonstrated to have an oncogenic function in carcinogenesis. In order to address the oncogenic capacity of CYP26A1 in vivo, transgenic mice that ubiquitously overexpressed CYP26A1 driven by the cytomegalovirus promoter were generated in the present study. Since the growth of these animals was normal for ≤15 months and they presented no evident abnormalities, a two-stage skin carcinogenesis analysis was performed. In the CYP26A1 transgenic mice, papilloma formation was observed within 7 weeks after administration of the carcinogen 7,12-dimethylbenz[a]anthracene (DMBA). Development of papillomas in these animals was significantly accelerated when compared with that observed in the control mice following treatment with DMBA in combination with the chemical tumor promoter 12-O-tetradecanoylphorbol-13-acetate. In addition, constitutive expression of CYP26A1 increased the susceptibility of these mice to the generation of squamous cell carcinomas caused by treatment with the carcinogen alone. It is thus concluded that CYP26A1 expression promotes skin carcinogenesis initiated by DMBA.